Efficacy and Safety of Piperacillin-Tazobactam and Cefepime as Empirical Therapy for Febrile Neutropenic Children with Acute Lymphoblastic Leukaemia (ALL) (Bangladesh Journal of Child Health, 2022)
Background: Infection is a major clinical challenge in ALL treatment. Prompt administration of empirical antibiotic in febrile neutropenic patients has reduced the mortality. Both Cefepime or Piperacillin-Tazobactam has been used as empirical treatment.Objective: To compare the efficacy and safety between Piperacillin-Tazobactam with Cefepime in febrile neutropenic children with ALL.Materials and methods: This randomized study was conducted from August 2015 to August 2016 in BSMMU. Sixty one episodes of febrile neutropenia in children with ALL, aged 0 to18 years were included in this study. Patients were randomized into two groups. One group received Piperacilln/Tazobactam and another group received Cefepime and data of 60 febrile neutropenic episodes were analyzed.Results: Febrile neutropenic episodes in the Piperacillin/Tazobactam group were 28 and in Cefepime group was 32 episodes and 34(57.63%) were male and 25 (42.37%) female. Median age was 5 years and 38(62.3%) neutropenic episodes were in induction phase. Majority had fever without focus 21(35%). Microorganisms isolated in 13 (21.66%) patients and majority 6 (46.15%) had blood infection. Most of the isolated organisms were Gram negative 11(84.61%). Overall treatment success without modification in the Piperacillin/Tazobactam group was 17(60.7%) and in Cefepime group 18 (56.3%) and that comparison was not statistically significant (p= 0.732). Significant difference was also not found comparing the mean duration of fever, neutropenia and hospital stay.Conclusion: Both Piperacillin/Tazobactam and Cefepime were found effective and safe as an empirical therapy for febrile neutropenic children with ALL.BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 83-88